Anthropometry of Agricultural Workers of Madhya Pradesh - AGRAWAL, K N; TIWARI, P S; GITE, L P; PHARADE, S; MAJUMDAR, J; BHUSHANABABU, V (Journal of Agricultural Engineering, 2012)
A study was undertaken to create the repository of anthropometeric data of agricultural workers of central India. Based on the population of male as well as female agricultural workers in twenty districts from nine different agro climatic zones of Madhya Pradesh (central India), data on seventy-nine identified body dimensions were collected for 1701 agricultural workers (944 male and 757 female). The selected workers were within the age group of 18-60 years with average age as 29.8 years for male and 33.7 years for female. Among the selected subjects, 7.4% male and 8.1% female workers were prominently using their left hand rather than right hand. The mean (±SD) weight and stature were 51.2±6.4 kg and 1649±59 mm for male, and 45.0±7.3 kg and 1519±54 mm for female workers, respectively. Vertical measurements had fairly good correlation with stature with coefficient of correlation(r) varying from 0.75-0.9 for both male and female workers. Similarly, vertical grip reach sitting, sitting eye height, and sitting acromion height had linear correlation with sitting height (r=0.75-0.85). The mean stature of male workers of Gujarat was higher than that of Madhya Pradesh, while the stature of all other population groups was lower. However, no such trend was observed among the female population of different states of the country. The 5th percentile values should be used for design where the lower limit is the restrictive factor such as operating forces, control reach and height of displays. The 95th percentile value should be used for design, where the upper limit is the restrictive factor such as design of clearances, seat width, backrest width and strap length for knapsack sprayers.